Adapting the Common European Framework of Reference for Languages to Croatian as Second and Foreign Language - Cvikić, Lidija; Jelaska, Zrinka (2005)
Ever since the term communicative (competence) was introduced into second language learning and it was attached to language learning programs based on notional-functional syllabus, the Communicative Language Teaching (CLT) has been the leading approach in the second language classroom and van Ek's Threshold Level engendered the Common European Framework of Reference for Languages. The possibilities of usage of the Common European Framework (CEF) and the European Language Portfolio (ELP) in second language learning, teaching and assessment are still explored, especially for the "world languages", i.e. English, German, Spanish, French etc. However, for the less-widely learned languages, like Croatian, their role might be even greater. Since the research of language acquisition and learning process, studies in teaching methods and development of curriculum, syllabus and teaching materials in less-widely learned languages are limited by materials as well as human sources, CEF is a good base and starting point for all of them. This paper deals with the role of CEF in the construction of the program of an intensive course in Croatian as second language.
Alkalmazott Nyelvészeti Konferencia füzetei ; ISSN 1586-6785
Projekt MZOS
ENG